2018
DOI: 10.1111/acem.13360
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Examination for Acute Aortic Dissection: A Systematic Review and Meta‐analysis

Abstract: Suspicion for acute aortic dissection should be raised with hypotension, pulse, or neurologic deficit. Conversely, a low AHA ADD score decreases suspicion. Clinical gestalt informed by high- and low-risk features together with an absence of an alternative diagnosis should drive investigation for acute aortic dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
34
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 39 publications
1
34
0
3
Order By: Relevance
“…Only studies of Armstrong, Eagle and Enia report on an isolated pulse deficit with a combined sensitivity of 24% (95% CI 13% to 41%) and specificity of 92% (95% CI 86% to 96%), which is similar to our results 10. Klompas’ review article in 2002 reported a similar diagnostic accuracy for the combined variable of systolic BP differential/pulse deficit with a positive likelihood ratio of 5.7 (1.4–23) and a negative likelihood ratio of 0.7 (0.6–0.9).…”
Section: Discussionsupporting
confidence: 91%
“…Only studies of Armstrong, Eagle and Enia report on an isolated pulse deficit with a combined sensitivity of 24% (95% CI 13% to 41%) and specificity of 92% (95% CI 86% to 96%), which is similar to our results 10. Klompas’ review article in 2002 reported a similar diagnostic accuracy for the combined variable of systolic BP differential/pulse deficit with a positive likelihood ratio of 5.7 (1.4–23) and a negative likelihood ratio of 0.7 (0.6–0.9).…”
Section: Discussionsupporting
confidence: 91%
“…The general diagnostic accuracy of CR for AASs was modest and lower than predicted, in spite of specialized, focused, and nonurgent evaluation of radiologic films by dedicated radiologists. In previous studies, the sensitivity of CR for AASs was highly variable (11%–94%), with a pooled sensitivity of 64% in a metanalysis of 13 studies comprising 1,337 patients . Most were retrospective case–control studies comparing AASs with selected AltD and were poorly representative of ED case mixes.…”
Section: Discussionmentioning
confidence: 99%
“…41 Based on previous data, in terms of specificity, we speculate that the ADD-RS/DD rule-out pathway could best apply to stable patients with ADD-RS = 1 owing to clinical manifestations providing per se higher specificity (i.e., pulse deficit, neurologic deficit, aortic valve insufficiency). 42 Caution is needed in patients with hypotension, which also potentially defines clinical instability and might prompt toward a fast track for advanced imaging irrespective of DD test results. However, in clinical practice, most cases with ADD-RS = 1 will be driven by pain features (severe, sudden, ripping pain), providing higher sensitivity but lower specificity.…”
Section: Discussionmentioning
confidence: 99%